Quiet influence : the introvert's guide to making a difference - Kahnweiler, Jennifer B. (San Francisco : Berrett-Koehler Publishers, 2013)
Introverts Do It Quietly Introverts may feel powerless in a world where extroverts seem to rule, but there?s more than one way to have some sway. Jennifer Kahnweiler proves introverts can be highly effective influencers when, instead of trying to act like extroverts, they use their natural strengths to make a difference. Kahnweiler identifies six unique strengths of introverts and includes a Quiet Influence Quotient (QIQ) quiz to measure how well you?re using these six strengths now. Then, through questions, tools, exercises, and powerful real-world examples, you will increase your mastery of these strengths.
Preface -- Introduction: why quiet influence, why now? -- Stop trying to act like an extrovert -- The six strengths of quiet influencers -- Your quiet influence quotient (QIQ) -- Quiet influence strength #1: Taking quiet time -- Quiet influence strength #2: Preparation -- Quiet influence strength #3: Engaged listening -- Quiet influence strength #4: Focused conversations -- Quiet influence strength #5: Writing -- Quiet influence strength # 6: Thoughtful use of social media -- Making a quiet difference -- Your quiet influence quotient (QIQ) self-assessment product -- Acknowledgments -- Notes -- Index -- About Jennifer -- Working with the author.
Includes bibliographical references (pages 153-162) and index.
Keywords: Interpersonal communication; Introverts; Interpersonal communication; Introverts; Communication; Interpersonal Relations; Introversion (Psychology)